The relationship between plasminogen activator inhibitor-1 and insulin resistance in newly diagnosed type 2 diabetes mellitus. - Gough, S; Rice, P; McCormack, L; Chapman, C; Grant, P (1993)
It is not clear whether elevated levels of the fibrinolytic inhibitor, plasminogen activator inhibitor-1 (PAl-1) in Type 2 diabetes mellitus are the result of obesity or coexistent atherosclerosis. Therefore the relationship between PAl-1 and insulin resistance, determined by the homeostasis model assessment (HOMA) was investigated in a group of 26 insulin-resistant, normotensive newly diagnosed Type 2 diabetic patients with a low probability of atherosclerosis. Compared with a normal control group, closely matched for body mass index (BMI), fibrinolytic activity was depressed in the diabetic patients due to elevated levels of the inhibitor PAl-1, 17.6 (11.1-28) vs 8.4 (4.9-14.1) IU ml-1, p < 0.001. PAl-1 was related to BMI, r = 0.59, p < 0.001 plasma insulin, r = 0.66, p < 0.001; insulin resistance, r = 0.54, p < 0.005 and urinary albumin excretion, r = 0.48, p < 0.01, but not HbA1c or fasting glucose. PAl-1 was not related to blood pressure or plasma triglyceride levels. This study suggests that at the time of diagnosis of Type 2 diabetes mellitus, elevated PAl-1 levels are already linked to other risk factors for vascular disease including hyperinsulinaemia, insulin resistance, and urinary albumin excretion, and this is not the result of obesity or coexistent atherosclerosis.